2019
DOI: 10.1038/s41598-019-55436-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal androgen excess on the male reproductive axis

Abstract: Prenatal androgen excess is suspected to contribute to the development of polycystic ovary syndrome (PCOS) in women. Evidence from preclinical female animal models links maternal androgen excess with the development of PCOS-like features and associated alterations in the neuronal network regulating the reproductive axis. There is some evidence suggesting that maternal androgen excess leads to similar reproductive axis disruptions in men, despite the critical role that androgens play in normal sexual differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…Confocal analysis of close appositions between NPY ARN neurons fibers and GnRH neurons found no differences in the NPY ARN -to-GnRH neuron projection in PCOS-like PNA females. These findings suggest that this subset of GABA ARN neurons are distinct to those that are remodeled by prenatal androgen excess [ 14 , 16 , 18 ]. Although NPY ARN neurons were found to have virtually no co-expression with PR and ERα, irrespective of prenatal treatment, we did observe a greater proportion of NPY ARN neurons co-expressing AR in PNA-treated mice, suggesting an upregulation of AR in NPY ARN neurons in the PCOS-like condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal analysis of close appositions between NPY ARN neurons fibers and GnRH neurons found no differences in the NPY ARN -to-GnRH neuron projection in PCOS-like PNA females. These findings suggest that this subset of GABA ARN neurons are distinct to those that are remodeled by prenatal androgen excess [ 14 , 16 , 18 ]. Although NPY ARN neurons were found to have virtually no co-expression with PR and ERα, irrespective of prenatal treatment, we did observe a greater proportion of NPY ARN neurons co-expressing AR in PNA-treated mice, suggesting an upregulation of AR in NPY ARN neurons in the PCOS-like condition.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy was performed using a Nikon A1R multi-photon microscope (Nikon Instruments Inc., Melville, NY, USA) to collect images of individual GnRH neurons in the MS, rPOA, and AHA. As reported previously [ 14 , 16 , 18 ], in each animal, z-stack confocal images were collected from 5 GnRH neurons in the MS and AHA, and 10 GnRH neurons in the rPOA, reflecting their distribution density. Using a Plan-Neofluar 40X oil objective (1.30 NA) and 3× digital zoom, scans throughout the soma and the first 75 µm of the primary dendrite of each GnRH neuron were performed using 0.5 µm z-intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Sections containing the rostral preoptic area (rPOA) were selected from a single 1:3 series and washed thoroughly in TBS before staining for vesicular γ-aminobutyric acid transporter (VGAT) and GFP (to visualise GnRH neurons). Free-floating immunohistochemistry was performed as reported previously 20,31,32 with primary antibody omission serving as a negative control. Briefly, sections were blocked with 2% normal goat serum (NGS) in TBS with 0.3% Triton X-100 and 0.25% bovine serum albumin (BSA) for 30 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…GnRH neurons (8-10 per animal) were randomly selected across two representative rPOA sections from each animal (DHT, n = 6; blank, n = 6) and images were captured at 40× magnification (0.5μm Z-step, 1 AU pinhole, digital magnification 2×). Using NIS-Elements AR 4.5 (Nikon Instruments Inc.), images were analysedfor VGAT appositions and GnRH spines on the GnRH neuron soma and at intervals of 15 μm along the primary dendrite as previously described 20,31,32. VGAT puncta were considered in close apposition to GnRH neurons when there was an absence of black pixels between the cyan and magenta signals.…”
mentioning
confidence: 99%
“…In humans, use of endocrine disruptors by pregnant women, for example, has been shown to be associated with future infertility in their male offspring 7 . Holland et al demonstrated that there is no effect of a maternal androgenic environment (due to polycystic ovarian syndrome) on the male reproductive axis 8 , while Lessard et al demonstrated that prenatal exposure to persistent organic pollutants reduced semen quality in male offspring 9 . After the onset of puberty, with the development of secondary sexual traits, spermatogenesis initiates, during which there are a number of conditions that may affect the quality of ejaculates—varicocele, for example, is detected in up to 80% of men with secondary infertility 10 , while testicular heat stress, in bovines, is a cause for lower fertility rates in sires 11 .…”
mentioning
confidence: 99%